Ascorbyl and hydroxyl radical generation mediated by a copper complex adsorbed on gold. Issue 37 (9th September 2019) - Romo, Adolfo I. B.; Dibo, Vitória S.; Abreu, Dieric S.; Carepo, Marta S. P.; Neira, Andrea C.; Castillo, Ivan; Lemus, Luis; Nascimento, Otaciro R.; Bernhardt, Paul V.; Sousa, Eduardo H. S.; Diógenes, Izaura C. N.
Abstract : Electrochemistry, nuclease assays, and EPR were used to detect ascorbyl and hydroxyl radical generation by a copper complex adsorbed on gold. Abstract : This work presents the results obtained for a thioether derivative of bipyridine, ( E, Z )-1-(4′-methyl-[2, 2′-bipyridine]-4-yl)- N -(4(methylthio)phenyl)methanimine (4-mbpy-Bz-SMe), and its copper complex [Cu II (4-mbpy-Bz-SMe)2 ] 2+ . Electronic spectra acquired at 183 K of the cuprous complex [Cu I (4-mbpy-Bz-SMe)2 ] + generated in situ indicated the formation of the peroxodicopper compound {[Cu II (4-mbpy-Bz-SMe)2 ]2 (μ-O2 2− )} 2+ . A gold electrode modified with [Cu II (4-mbpy-Bz-SMe)2 ] 2+ (Au/[Cu]) was fully characterized by SERS spectroscopy, electrochemistry and impedance spectroscopy thus showing adsorption occurs through the sulfur atom of the 4-mbpy-Bz-SMe moieties. DNA cleavage assays showed the copper complex, in solution and adsorbed on gold, degrades DNA if reducing conditions are maintained, i.e. ascorbic acid (H2 AA) in solution or applied potentials more negative than 0.12 V vs. Ag/AgCl (Cu I form). The electron paramagnetic resonance (EPR) spectra obtained for the electrolyzed solution ( E apl = −0.2 V, no H2 O2 ) and for the solution containing [Cu II (4-mbpy-Bz-SMe)2 ] 2+ and H2 O2 showed hydroxyl radical, HO˙, generation had occurred. The cyclic voltammograms obtained with H2 AA in solution at Au/[Cu II (4-mbpy-Bz-SMe)2 ] 2+ as the working electrode showed a one-electron reaction leading to the ascorbyl radical (HA˙), which was detected by EPR. The current assigned to the electrode oxidation of HA˙ to AA decreased with the addition of catalase, a scavenger of H2 O2, meaning peroxide is involved in the mechanism.